Evaluation of nutrient content of chia flour (Salvia hispanica L.) and sesame flour (Sesamum indicum L.) as alternative flour rich in fiber and protein - Imas Arumsari; Mira Sofyaningsih (UHAMKA PRESS, 2020)
There is a growing interest on using alternative substitution of food ingredients which aims to delay postprandial blood glucose, such as protein and fiber, to reduce the risk of metabolic syndrome that leads to non-communicable diseases (NCDs). This research aims to evaluate the nutrient content of chia seed flour (TC) and sesame seed flour (TW) as alternative flour rich in fiber and protein which potential to reduce the risk of NCDs. Proximate analysis (protein, fat, carbohydrate, water, ash), fiber, and calcium analysis were done for two types of flour. The results showed that TW is rich in fat (58,90 ± 0,07 g/100g) while TC rich in protein (26,23 ± 0,06 g/100g), fiber (30,24 ± 0,08 g/100g), and calcium (617,05 ± 24,74 mg/100g). In conclusion, TW and TC are potential to use as substitution of wheat flour for bakery products, as consideration to increase nutritional value of the product. Keywords: Chia Flour, Non-Communicable Diseases, Sesame Flour